Rancang Bangun Sistem Pencarian Posisi Kendaraan di Area Parkir Menggunakan Teknologi Bluetooth - Fahrudin Mukti Wibowo; Fikra Titan Syifa (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Large parking area and no sign, will make it difficult for vehicle owners to remember and find the location of the parked. Therefore, a guide system becomes one of the important things in a large parking area. The technology that can be utilized in navigation systems is bluetooth technology, which has now called BLE (Bluetooth Low Energy) with a signal reach of 100 meters, data transfer speeds 1 Mbps and low power consumption. The information from a BLE module is the value of RSSI (Received Signal Strength Indicator) which shows the signal strength received. The guide system installed on a smartphone as a receiver and BLE module as a transmitter on the vehicle. The mobile application will convert the RSSI into the distance between smartphone and vehicle, and will be displayed a guide to the vehicle. Based on the trials that have been carried out obtained an average distance error of 0.92 meters, this is due to the ups and downs of the RSSI value received. When the RSSI value received is small, it raises of accuracy. So the distance between BLE and receiver will affect the RSSI value received and affect the position accuracy of the application.